The Firm in Short-Run Industry Equilibrium: Comment - Braulke, Michael (American Economic Review, 2016)
It has long been recognized that the traditional law of supply and demand valid for the isolated competitive firm need not necessarily hold when considering the individual firm within the greater context of its industry. Indeed, a change in a certain input or output price will in general affect all input and output decisions, and these reactions can be expected to trigger other price changes at the industry level in those markets where the industry faces less than infinitely elastic supply or demand. The initial response of the individual firm to the original price change may thus be altered by its response to these consequent price changes and perhaps even be completely reversed. In his 1982 paper, Ronald Heiner has shown for the special yet important case of an infinitely elastic supply in all factor markets that at least the law of demand will nevertheless hold in the short run for the entire industry, provided that demand for its output is normal in the usual sense of a downward-sloping schedule. This reassuring result is noteworthy in itself, but it also commands admiration because it represents one of the few cases where an ambiguity at the micro level is resolved at the macro level by aggregation. Heiner goes even further in the characterization of the industry's shortrun response by saying that it will be weaker than the response that would arise if demand in the output market were infinitely elastic and conversely stronger than the response that would result if demand in the output market were entirely inelastic (pp. 555-56). Yet in his formal analysis Heiner proves a somewhat different (and weaker) version of this characterization by showing that the industry's short-run response must be stronger than the response that would be observed if the output of every firm were fixed. It is the purpose of this comment to show that Heiner's intuitively more appealing original contention indeed holds and in fact characterizes the industry's short-run response more precisely than the version that was actually proven. At the same time, and perhaps more interestingly, I want to generalize Heiner's findings by showing that they in essence still apply if the industry also faces in some of its input markets a less than infinitely elastic (but normal) supply. This generalization is obviously relevant for all those industries that are the sole users, or at least major users of certain inputs and hence not necessarily small in relation to the size of these input markets. By generalizing Heiner's notation, I use a framework that allows us to deal with an arbitrary number of inputs and outputs and, in particular, with an arbitrary number and combination of markets in which the industry is confronted with a less than infinitely elastic demand or supply.